Sosialisasi, Instalasi, dan Penggunaan Software Open-Source LibreOffice Writer bagi Guru di Kabupaten Bantaeng - Mas'ud, Syamsuddin; Syam, Rahmat; Ihsan, Hisyam (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Partnership Program (PKM) activities are carried out in Bantaeng Regency, South Sulawesi Province. The partners in this PKM activity are the teachers from the Mathematics Subject Teachers' Meeting (MGMP) at junior high schools (SMP) in Bantaeng Regency. However, in its implementation, in addition to SMP teachers, it is also attended by elementary school (SD), high school (SMA), and vocational high school (SMK) teachers. Among the objectives of this program are a) Socializing open-source software LibreOffice as an alternative to licensed Microsoft Office software; b) Providing knowledge to partners about the installation of LibreOffice software and the basics of using LibreOffice Writer. Some of the issues faced by the partners include a) knowledge about open-source software; b) Installation and basics of using LibreOffice Writer. This socialization and training are carried out for a group of partners, consisting of approximately 11 people, through online sessions via Zoom meetings. The expected outcomes are an understanding of the socialization materials, the installation of the application, and the basics of using the LibreOffice Writer application.